The problem of the criminal method: Arturo Rocco (2011)
Is the dogmatic the criminal method by excellence? It could be, but today it’s imposed the needs of overthinking and understanding from the acceptance of its new challenges and possibilities, such as the legal actors multiplicity and the Jurisprudence as